2022
DOI: 10.1002/1873-3468.14496
|View full text |Cite
|
Sign up to set email alerts
|

Myelin‐associated glycoprotein alters the neuronal secretome and stimulates the release of TGFβ and proteins that affect neural plasticity

Abstract: Myelin‐associated glycoprotein (MAG) and Nogo inhibit neurite outgrowth by binding to receptors such as NgR1, PirB and LRP1, and they have also been shown to induce phosphorylation of Smad2, a key intermediate in the transforming growth factor β (TGFβ) signalling pathway. In this study, we determined that MAG and Nogo do not transactivate the TGFβ receptor through their canonical receptors or discoidin domain receptor 1, which we identified as a novel receptor for MAG and Nogo. Instead, MAG and Nogo promoted S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 127 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…The presence of S100A6 has been reported for example in the culture medium of decidual cells [ 142 ] or cerebellar granule neurons treated with myelin-associated glycoprotein [ 143 ]. It has been also detected in extracellular matrix of Wharton’s jelly [ 144 ], amnion fluid [ 145 ], pancreatic juice [ 107 , 146 ], urine [ 147 , 148 ] and tears [ 149 ]. Recent results have shown that S100A6 is present in nasal lavage fluid [ 150 ], and its level is elevated in the nasal swabs of COVID-19 patients [ 151 ].…”
Section: Extracellular S100a6—a Marker Of Pathological Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of S100A6 has been reported for example in the culture medium of decidual cells [ 142 ] or cerebellar granule neurons treated with myelin-associated glycoprotein [ 143 ]. It has been also detected in extracellular matrix of Wharton’s jelly [ 144 ], amnion fluid [ 145 ], pancreatic juice [ 107 , 146 ], urine [ 147 , 148 ] and tears [ 149 ]. Recent results have shown that S100A6 is present in nasal lavage fluid [ 150 ], and its level is elevated in the nasal swabs of COVID-19 patients [ 151 ].…”
Section: Extracellular S100a6—a Marker Of Pathological Statesmentioning
confidence: 99%
“…However, it was proposed to regulate secretory processes since, when added to the medium, it stimulated the secretion of lactogen II by trophoblast cells [ 142 ] and the release of insulin from pancreatic cells [ 41 , 152 ] and of histamine from mast cells [ 153 ]. In the case of mesenchymal stem cells of the Wharton’s jelly extracellular S100A6 caused an increase in cell adhesion and, contrary to the intracellular protein, inhibited their proliferation [ 144 ].…”
Section: Extracellular S100a6—a Marker Of Pathological Statesmentioning
confidence: 99%